Modeling phreatic levels in a rural watershed in lontras, high itajaí valley, SC-Brazil - de Melo, Mateus Nascimento Vieira; Manzione, Rodrigo Lilla [UNESP]; Pinheiro, Adilson; Piazza, Gustavo Antonio; Torres, Edson; Kaufmann, Vander (Lepidus Tecnologia, 2020)
This study analyzed the behavior of phreatic levels in a rural watershed located the municipality of Lontras, High Itajaí Valley, Santa Catarina, Southern Brazil. Phreatic levels are monitored by 3 wells (PZMC located in riparian forests and PZ2127 and PZ3 in pasture areas). Rainfall and fluviometric level are also monitored. Fluviometric station is located near PZ2127. Daily evapotranspiration was calculated using the Samani method. Monitoring was performed from January 1, 2012 to July 15, 2019, combining 7.5 years of data. An exploratory data analysis and a trend analysis of groundwater levels was performed. Simulation was performed with the PIRFICT model (from December 31, 2014 to January 19, 2016). Trend analysis identified significant decay trends for PZMC and PZ3, and elevation trends for PZ2127. The PIRFICT model presented acceptable adjustments. The errors were low and it was possible to characterize the dynamic impulse response relationship between the explanatory variables and the observed levels. The information obtained from the phreatic levels monitoring and modeling proved to be necessary for the local groundwater resources management, providing support for planning and decision making.
Modelagem de níveis freáticos em uma bacia hidrográfica rural em lontras, alto vale do Itajaí, SC
Keywords: Impulse response functions; Monitoring; Phreatic levels; PIRFICT model